Trauma and Protest inTtestimonies of Chilean Exile - Peris Blanes, Jaume (Anales de Literatura Hispanoamericana, 2009)
The article analizes the role accomplished by the testimonies of survivors of concentration camps in Chile, wich were published in the early years after the military putsch of Pinochet on 1973. The article focuses in two main elements. On one hand, the role accomplished by testimonies in the international protests against the Pinochet dictatorship. On the other hand, the way they used the witness writing for working through their trauma of violence.
Keywords: Testimony; Chile; Exile; Repression; Concetration camps; Memory